Radiometric Stability of the SABER Instrument. Issue 2 (15th February 2020) - Mlynczak, Martin G.; Daniels, Taumi; Hunt, Linda A.; Yue, Jia; Marshall, B. Thomas; Russell, James M.; Remsberg, Ellis E.; Tansock, Joseph; Esplin, Roy; Jensen, Mark; Shumway, Andrew; Gordley, Larry; et al.
Abstract: The SABER instrument on the National Aeronautics and Space Administration Thermosphere‐Ionosphere‐Mesosphere Energetics and Dynamics satellite continues to provide a long‐term record of Earth's stratosphere, mesosphere, and lower thermosphere. The SABER data are being used to examine long‐term changes and trends in temperature, water vapor, and carbon dioxide. A tacit, central assumption of these analyses is that the SABER instrument radiometric calibration is not changing with time; that is, the instrument is stable. SABER stratospheric temperatures and those derived from Global Positioning System Radio Occultation measurements are compared to examine SABER's stability. Global Positioning System Radio Occultation measurements are inherently stable due to the accuracy and traceability of the measured phase delay rate to the Système Internationale definition of the second. Differences in global annual mean SABER and COSMIC lower stratospheric temperatures show little significant change with time in the 11 years spanning 2007–2017. From this analysis we infer that SABER temperatures are stable to better than 0.1 to 0.2 K per decade. Plain Language Summary: SABER is an instrument that has been in orbit on the National Aeronautics and Space Administration Thermosphere‐Ionosphere‐Mesosphere Energetics and Dynamics satellite for over 18 years, observing temperature and composition of the atmosphere from 15 to over 100 km in altitude. Over this time the atmosphere has undergone changes. A key to diagnosing these changes is knowing that the SABER instrument itself has not been changing and so observed atmospheric changes are in fact real. This paper presents an analysis of SABER temperatures in the Earth's lower stratosphere (15‐ to 35‐km altitude) relative to those derived from Global Positioning System‐Radio Occultation (GPS‐RO) measurements of atmospheric refraction. The GPS‐RO temperatures are inherently stable due to their traceability to the definition of the second. The analysis of SABER and GPS‐RO temperatures shows that the SABER instrument is remarkably stable, better than 0.1 to 0.2 K per decade. Key Points: SABER is remarkably stable, with less than 0.1 to 0.2 K per decade drift relative to inherently stable temperatures from GPS‐RO sensors SABER stability should be included in the uncertainty estimates of derived temperature trends in the middle atmosphere Deliberate emphasis on accurate calibration from project start drove instrument design choices that enabled SABER stability